Caracterização de metadiamictitos ferruginosos da Formação Nova Aurora (Grupo Macaúbas, Orógeno Araçuaí) a Oeste de Salinas, MG - Francisco Teixeira Vilela (2010)
The iron-bearing metadiamictites of the Riacho Poções Member (Nova Aurora Formation, Macaúbas Group) are known since the 1920s, but the first detailed studies were carried out in the 1970s concerning exploration purposes. However, it lacks studies on the genesis of those iron-bearing metadiamictites, even though an origin related to a glacial event is widely accepted for the diamictitic formations of the Macaúbas Group. A Neoproterozoic age for this group is reported by many authors that also suggest a correlation of their glaciogenic deposits with the Sturtian glaciation event. In fact, an important feature of the Neoproterozoic iron deposits is the association with glaciation events. This MSc dissertation focuses on the petrographic, mineragraphic and geochemical characterizations of ferruginous metadiamictites and their host rocks, mainly carried out from studies on drill core samples. The Riacho Poções Member iron deposit consists of metadiamictites with hematite and/or magnetite as matrix components. These rocks were deposited in a continental rift basin during a glacial event. The deposits, as well as the whole Macaúbas Group, were deformed and metamorphosed in the Late Neoproterozoic Araçuaí Orogen. The iron-bearing metadiamictites record three deformational phases: D1, D2 and D3. The west-verging, tight asymmetric folding and its axial-plane, east-dipping S1 schistosity characterizes the D1 phase. D2 phase is east-verging and show cascade asymmetric folds associated with the axial-plane, west-dipping, crenulation foliation S2. Ductile shear zones associated to D1 and D2 phases had great influence on the concentration of specular hematite and dissolution of gangue minerals. The last deformational phase, D3, is characterized by two systems of widely spaced fractures, trending NW and NE, which seem to be associated with large regional flexures. The Fe2O3(t) contents of the ferruginous metadiamictites vary from 13 to 78%. Correlation diagrams comparing Fe2O3(t) and elements of siliciclastic origin suggest that the iron-rich compounds (i.e., iron hydroxides) were chemically precipitated coeval with the debris flow sedimentation at the end of a glacial event. Those compounds were recrystallized as hematite and specularite during D1 and D2 phases. The magnetite features suggest a late D1 to late D2 origin.